Pengembangan Aplikasi Live Chat Menggunakan Extreme Programing - Permana, Edwar; Sutedi, Ade; Elsen , Rickard (Institut Teknologi Garut, 2024)
Reservations are a form of service provided by companies for arranging or ordering, for example, tickets, tables, hotel rooms for someone at a certain time. There are many ways to provide reservation services, one of which is through communication media. This research is a development of